The Effect of Squid (Loligo sp.) Bone Chitosan Powder on Total Cholesterol Levels of Rats (Rattus norvegicus) - Indah Indah; Muhammad Asri; Suryanita Suryanita; Astika Irianti (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2024)
Bones in squid (Loligo sp.) can be used as a source of medicinal ingredients, one of which is chitosan. The polymer in chitosan contains amino and hydroxyl groups per residue, giving chitosan many biological activities, such as anti-inflammatory, antimicrobial, hypoglycemic, hypocholesterolemic, and immunostimulatory effects. This study aims to determine the antioxidant activity and the effect of chitosan squid bone powder on the total cholesterol levels of rats (Rattus norvegicus). This type of research used an experimental method with a one-group pre-test and post-test design, in which 12 male white rats, body weight 150 g, were divided into four groups. Group 1 was a negative control of 1% Na-CMC, group II chitosan 50 mg/kg, group III chitosan 100 mg/kg, and group IV positive control of simvastatin 10 mg, which each group was given orally; the treatment was carried out for two weeks. The results showed a decrease in the mean after treatment in the treatment group with chitosan powder, but there was no significant difference compared to the control group (P>0.005). This shows that squid bone chitosan powder reduced total cholesterol levels in rats.